Enhanced electromagnetic interference shielding effectiveness of h-BN decorated micro cube-like CaTiO3/Cu nanocomposite. Issue 6 (15th March 2022) - Fan, Guangli; Xiong, Tiantian; Mouldi, Abir; Bouallegue, Belgacem; Tran, Ngo; Mahmoud, Mustafa Z.
Abstract: Due to the balance of dielectric and magnetic losses achieved by impedance matching, combining dielectric and magnetic materials might result in potential microwave absorbers. However, some dielectric/ferromagnetic materials could also be used as good microwave absorbers, such as CaTiO3 . In order to improve the microwave absorption features of CaTiO3, we fabricated two CaTiO3 -based composites as CT/C (CaTiO3 /Cu) and CT/C/B (CT/C/hexagonal boron nitride, h -BN). By decorating h -BN, the CT/C/B achieved a large specific area and a high total pore volume, which was beneficial to the microwave absorption performance in f  = 8.2–12.4 GHz of CT/C/B compared to that of CT/C. The reflection loss (RL) was reasonably good as −15 dB for CT/C composite, while CT/C/B could reach the RL of −40 dB. Better microwave absorption dissipation features of CT/C/B compared to CT/C could result from higher electrical conductivity, attenuation constant, and lower skin depth. The presence of h -BN in the composite could also tune the total shielding effectiveness of CT/C/B to 32.5 dB, which was equal to 1.4 times compared to that of CT/C (23.5 dB).